The Role of School Culture Based on Islamic Values in Shaping Students' Character at Pratheep Vittaya School Narathiwat Thailand - Rahmah Suaibah; Darliana Sormin; Adek Kholijah Siregar (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the role of school culture in shaping the character of students at Prateep Vittaya School, Thailand. This study uses a qualitative approach with a field study design to gain an in-depth understanding of the implementation of school culture based on Islamic values. Data collection techniques include participant observation, in-depth interviews, and documentation, with teachers and students as key informants. Data analysis was carried out using the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawn, as well as testing the validity of the data through triangulation. The results of the study show that school culture plays an important role in shaping students' character, especially in the dimensions of religiosity, discipline, responsibility, and independence. This is reflected in routine activities such as congregational prayers, the implementation of the 5S culture (smile, greeting, greetings, manners), disciplined learning, maintaining cleanliness environment, and managing social interactions in accordance with Islamic principles, and life skills culture. The application of school culture based on Islamic values has proven to be consistently effective in shaping student character holistically and can become a paradigm for other educational institutions